Design and synthesis of plant oil-based UV-curable acrylates for sustainable coating applications - Sung, Jonggeun (Kansas State University, 2018)
A demand in sustainable polymers has been increased because of the environment concerns and saving finite petroleum resources. Plant oils are promising renewable resources to produce environmentally friendly polymer applications. Soybean oil-based resins such as epoxidized soybean oil (ESO) and acrylated epoxidized soybean oil (AESO) have been well-known functionalized plant oils, but relatively low performances of their polymers and a competition with food production have been disadvantages. Thus, in this study, we designed new plant oil-based acrylates using non-food resources and achieved excellent properties of the acrylates for coatings and thermoset applications. Firstly, we developed coating materials with high mechanical, thermal and coating performances using acrylated epoxidized camelina oil (AECO) as a main acrylate monomer with various meth(acrylates) as reactive diluents Next, acrylated epoxidized cardanol modified fatty acids from camelina oil (AECFA) was successfully synthesized, and a phenolic structure with long aliphatic side chains with acrylic groups was obtained. The novel structure of AECFA provided rigidity into its polymer maintained with flexibility, and AECFA coating material showed better performances in terms of all properties such as mechanical, thermal, viscoelastic, and coating performances, as compared to commercial AESO resin. Finally, acrylated epoxidized allyl 10-undecenoate (AEAU) was developed from 10-undecenoic acid, castor oil derivative. The single fatty ester structure with di-functional acrylates of AEAU had very lower viscosity and showed better thermoset performances than those of triglyceride-based acrylates such as AESO and AECO. Thus, AEAU had a potential to an alternative to AESO for thermoset applications.
Keywords: Bio-based coating material; UV-curing; Plant oil-based acrylate; Biopolymer; Industrial crop; Biothermoset